Work styles, attitudes, and productivity of scientists in the Netherlands and the United Kingdom: A comparison by gender - Dara L. Woerdeman; Yana van der Meulen Rodgers (Management Revue, 2006)
With scientific research growing increasingly multidisciplinary in nature, team playing and communication skills have become critical in the achievement of scientific breakthroughs. This study adds valuable evidence to the oft-cited 'productivity puzzle' in the sciences by comparing the work styles, attitudes, and productivity of female and male scientists. The application of t-test analysis to data on scientists from the United Kingdom and the Netherlands indicates that women report relatively higher abilities in communication skills and teamwork than men. Also, both female and male scientists report difficulties in balancing work and family responsibilities, but proportionately more women than men rely on outside sources of childcare. A separate distribution analysis of academic productivity demonstrates substantial overlap between men and women in the number of scientific publications per year. These results add support to mounting pressure for policy reforms that effectively support the retention and advancement of women in the sciences.
Keywords: 650; skills; workplace diversity; technical innovation; scientific output; women in science; science in Europe; Industrielle Forschung; Betriebliche Forschung; Unternehmenskooperation